PENGARUH PEMBERIAN STIMULASI PUTTING SUSU TERHADAP LAMA PERSALINAN KALA 1 PADA PRIMIGRAVIDA DI WILAYAH KERJA PUSKESMAS BALOI PERMAI KOTA BATAM - Intan Dwi Rahayu; Mona, Silvia; Jannah, Miftahul (Universitas Batam, 2025)
In the first stage of labor, the duration of labor dilation in primigravida mothers differs from that in multigravida mothers. This can be due to the mother's lack of experience in the labor process. The cause of the prolonged period of labor can be due to inadequate labor. Good contractions will facilitate the delivery process. In this study, a method that can be done to increase labor is by stimulating the nipples. This activity can be done by rubbing around the breasts or by gently massaging the nipples. The purpose of this stimulation is to trigger the release of the hormone oxytocin, which can help increase contractions and accelerate labor dilation. The purpose of this study was to determine the effect of nipple stimulation on labor duration in primiparous mothers in the Baloi Permai Community Health Center Work Area, Batam City in 2025. The research method used is quantitative research. The research design uses a group comparison design, with one group of the Control group that was not given treatment and one group in the Intervention Group that was given nipple stimulation treatment, the sample in this study was 30 primiparous mothers, the sampling technique used total sampling. Results and conclusions: after data analysis, a p value of 0.02 was obtained, which means p <0.05. This shows that there is an effect of nipple stimulation on the length of first stage of labor in the Baloi Permai Community Health Center Working Area, Batam City in 2025. Keywords: Nipple Stimulation, Duration of Labor, Primipara, Mother in Labor